2006
DOI: 10.1109/tns.2006.870174
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of high-energy contamination in SPECT imaging using Monte Carlo simulation

Abstract: 123 I is a commonly used radioisotope employed in neurotransmitter SPECT studies. In addition to an intense line at 159 keV, the decay scheme of this radioisotope includes a low yield ( 3%) of higher energy photons which make a non-negligible contribution to the final image when low-energy high-resolution (LEHR) collimators are used. This contribution of high-energy photons may reach 28% of the total counts in the projections. The aim of this work is to model each energy component of the high-energy Point Spre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Even though generating a table of depth-dependent CDRs with very low noise requires their computation only once, it is still computationally demanding [2]. There have been some efforts to develop faster MC simulations that include the septal penetration and collimator scatter response [9], [11], [15], but using a MC simulator as a forward projector involves high computational complexity [14]. In addition, one should validate the MC simulation by comparison of simulated energy spectra and PSFs with experimental measurements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though generating a table of depth-dependent CDRs with very low noise requires their computation only once, it is still computationally demanding [2]. There have been some efforts to develop faster MC simulations that include the septal penetration and collimator scatter response [9], [11], [15], but using a MC simulator as a forward projector involves high computational complexity [14]. In addition, one should validate the MC simulation by comparison of simulated energy spectra and PSFs with experimental measurements.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, one should validate the MC simulation by comparison of simulated energy spectra and PSFs with experimental measurements. For higher-energy photons it has been shown that it is important to carefully model all components of the SPECT detector system (collimator, back compartment, shielding) to get good agreement between measurement and simulation [9], [16], [17]. Even small discrepancies between collimator specification provided by the manufacturer and the actual dimensions of the collimator can lead to significant mismatch between measurement and simulation.…”
Section: Introductionmentioning
confidence: 99%
“…The aim of this study was to evaluate the image quality and quantify the impact of high energy contamination for each isotope. High energy contamination [4,5] ends up in the main energy window by one or by a combination of the following effects: scatter in the object, Compton effect in the crystal, penetration of the collimator, and backscatter from the camera end parts (light guides, PMTs, lead ending).…”
Section: Introductionmentioning
confidence: 99%
“…The model for high energy detection was also considered to be Gaussian [8]: Here, Xo and Yo are the coordinates of the perpendicular projection of the source point on the detector plane, x andy are coordinates for any point on this plane, b is a parameter determining the width of the Gaussian function and A represents its amplitude. Parameters A and b were measured from planar images of a small sphere containing 0.30 MBq of IS F, placed at increasing distances from 1 to 6 cm, at intervals of 1 cm.…”
Section: Displays the Spect System Andmentioning
confidence: 99%
“…In previous works, HE response functions based on MC simulation have been developed for human imaging gamma cameras and incorporated into SimSET [8], [5], [6]. While MC modeling of backscattering areas is a useful method, its accuracy is often compromised by the need to reduce 978-1-4673-0120-6/111$26.00 ©2011 IEEE computation time, and current models could still be improved [9].…”
Section: Introductionmentioning
confidence: 99%